. - María de la Luz Hurtado (Revista Chilena de Literatura, 2002)
Starting from the scriptural-pictorial text The Origin of the Two Fridas: Remembrance, a fragment in the Diary of this singular Mexican artist, the significance process (Kristeva) inscribed in the elaboration of the anamnesic account is inquired into, in order to arrive at relevant questions about cultural and genre studies; what creative processes does a woman like Frida realize, enabling her to manifest the slippery "feminine differential"? Is the identification by the established critique of the intimate with the feminine in her work but a way to leave out of the social and political field her creative production?